Advanced Small Animal Conformal Radiation Therapy Device. (February 2017) - Sharma, Sunil; Narayanasamy, Ganesh; Przybyla, Beata; Webber, Jessica; Boerma, Marjan; Clarkson, Richard; Moros, Eduardo G.; Corry, Peter M.; Griffin, Robert J.
We have developed a small animal conformal radiation therapy device that provides a degree of geometrical/anatomical targeting comparable to what is achievable in a commercial animal irradiator. small animal conformal radiation therapy device is capable of producing precise and accurate conformal delivery of radiation to target as well as for imaging small animals. The small animal conformal radiation therapy device uses an X-ray tube, a robotic animal position system, and a digital imager. The system is in a steel enclosure with adequate lead shielding following National Council on Radiation Protection and Measurements 49 guidelines and verified with Geiger-Mueller survey meter. The X-ray source is calibrated following AAPM TG-61 specifications and mounted at 101.6 cm from the floor, which is a primary barrier. The X-ray tube is mounted on a custom-made "gantry" and has a special collimating assembly system that allows field size between 0.5 mm and 20 cm at isocenter. Three-dimensional imaging can be performed to aid target localization using the same X-ray source at custom settings and an in-house reconstruction software. The small animal conformal radiation therapy device thus provides an excellent integrated system to promote translational research in radiation oncology in an academic laboratory. The purpose of this article is to review shielding and dosimetric measurement and highlight a few successful studies that have been performed to date with our system. In addition, an example of new data from an in vivo rat model of breast cancer is presented in which spatially fractionated radiation alone and in combination with thermal ablation was applied and the therapeutic benefit examined.